Upaya Meningkatkan Efektivitas Pembelajaran Pendidikan Kewarganegaraan melalui Metode Diskusi - Ahmad Jamalong; Indajati -- (Jurnal Pendidikan dan Kebudayaan, 2015)
The purpose of this research is to analyze the effectiveness of student learningÂ by using group discussion method. This research was conducted in seventh grade studentÂ of SMPN 1 Sungai Kunyit, Pontianak Regency, in the academic year of 2013/2014 by usingÂ classroom action research. The research subjects were the grade seven students thatÂ consisted of 31 students chosen by using random sampling. The data were collected byÂ using test and the action was applied by using classroom action research. The action wasÂ applied in 3 cycles on â€œhistory of Indonesia Independenceâ€. Every cycle consisted of fourÂ stages namely planning, action, observation and reflection. The finding of this researchÂ indicated that before conducting the action, there had not been any student who achievedÂ the minimum mastery level. After conducting the first action, the studentsâ€™ learning wasÂ recorded for 58.50. In second implementation of the action, the score increased to 67.09.Â After the implementation of cycle 3, the score again increased to 76.93 that exceeded theÂ minimum completion criteria that had been determined by school or civic education subject.Â This research concludes that the application of Group Discussion Method in civic educationÂ in SMPN 1 Sungai Kunyit improves the studentsâ€™ learning outcome.